Intergenerational effects on mouse sperm quality after in utero exposure to acetaminophen and ibuprofen. Issue 1 (6th July 2018) - Rossitto, Moïra; Marchive, Candice; Pruvost, Alain; Sellem, Eli; Ghettas, Aurélie; Badiou, Stéphanie; Sutra, Thibault; Poulat, Francis; Philibert, Pascal; Boizet-Bonhoure, Brigitte
ABSTRACT: Nonsteroidal antiinflammatory drugs and analgesic drugs, such as N ‐acetyl‐ p ‐aminophenol (APAP; acetaminophen, paracetamol), are widely used by pregnant women. Accumulating evidence has indicated that these molecules can favor genital malformations in newborn boys and reproductive disorders in adults. However, the consequences on postnatal testis development and adult reproductive health after exposure during early embryo‐genesis are still unknown. Using the mouse model, we show that in utero exposure to therapeutic doses of the widely used APAP‐ibuprofen combination during the sex determination period leads to early differentiation and decreased proliferation of male embryonic germ cells, and early 5‐mefhylcytosine and extracellular matrix protein deposition in 13.5 d postcoitum exposed testes. Consequently, in postnatal testes, Sertoli‐cell maturation is delayed, the Leydig‐cell compartment is hyperplasia and the spermatogonia A pool is decreased. This results in a reduced production of testosterone and in epididymal sperm parameter defects. We observed a reduced sperm count (19%) in utero –exposed (FO) adult males and also a reduced sperm motility (40%) in their offspring (Fl) when both parents were exposed, which leads to subfertility among the 6 mo old Fl animals. Our study suggests that the use of these drugs during the critical period of sex determination affects the germ‐line development and leads to adverse effects that could be passed to the offspring.—Rossitto, M., Marchive, C., Pruvost, A., Sellem, E., Ghettas, A., Badiou, S., Sutra, T., Poulat, F., Philibert, P., Boizet‐Bonhoure, B. Intergenerational effects on mouse sperm quality after in utero exposure to acetaminophen and ibuprofen. FASEB J. 33, 339–357 (2019). www.fasebj.org